Chemical Proteomics and Phenotypic Profiling Identifies the Aryl Hydrocarbon Receptor as a Molecular Target of the Utrophin Modulator Ezutromid. (3rd January 2020) - Wilkinson, Isabel V. L.; Perkins, Kelly J.; Dugdale, Hannah; Moir, Lee; Vuorinen, Aini; Chatzopoulou, Maria; Squire, Sarah E.; Monecke, Sebastian; Lomow, Alexander; Geese, Marcus; Charles, Philip D.; Burch, Peter; et al.
Abstract: Duchenne muscular dystrophy (DMD) is a fatal muscle‐wasting disease arising from mutations in the dystrophin gene. Upregulation of utrophin to compensate for the missing dystrophin offers a potential therapy independent of patient genotype. The first‐in‐class utrophin modulator ezutromid/SMT C1100 was developed from a phenotypic screen through to a Phase 2 clinical trial. Promising efficacy and evidence of target engagement was observed in DMD patients after 24 weeks of treatment, however trial endpoints were not met after 48 weeks. The objective of this study was to understand the mechanism of action of ezutromid which could explain the lack of sustained efficacy and help development of new generations of utrophin modulators. Using chemical proteomics and phenotypic profiling we show that the aryl hydrocarbon receptor (AhR) is a target of ezutromid. Several lines of evidence demonstrate that ezutromid binds AhR with an apparent KD of 50 nm and behaves as an AhR antagonist. Furthermore, other reported AhR antagonists also upregulate utrophin, showing that this pathway, which is currently being explored in other clinical applications including oncology and rheumatoid arthritis, could also be exploited in future DMD therapies. Abstract : Chemische Proteomik und phänotypisches Profiling zeigen, dass der Aryl‐Kohlenwasserstoff‐Rezeptor (AhR) ein Target von Ezutromid ist, dem ersten Utrophin‐Modulator zur Behandlung von Duchenne‐Muskeldystrophie. Ezutromid bindet an AhR mit einem effektiven K D von 50 nm und fungiert als AhR‐Antagonist. Andere AhR‐Antagonisten bewirken ebenfalls die Hochregulierung von Utrophin, was zeigt, dass dieser Weg auch in zukünftigen DMD‐Therapien genutzt werden könnte.